Political Apathy in Protecting Residential Environmental Problems in Banjarmasin City: Perspective from Residents in the Kelayan Riverbank - Armiah Armiah (Jurnal Studi Sosial dan Politik, 2022)
Settlement on the banks of the river in the city of Banjarmasin, requires a comprehensive arrangement. The support of the residents of the Kelayan riverbank is an absolute must. The Banjarmasin city government itself plays a role in implementing the environmental management of the Kelayan riverbank through two policies. Namely, arranging structurally and fostering culturally. It is hoped that these two mechanisms, apart from synergizing, also get maximum results in managing rivers in the city of Banjarmasin. For this reason, it is essential to see how residents perceive their settlements and the policies taken by the city government in managing them. This phenomenological research through FDG interviews showed that residents support every government effort and realize that their residential environmental problems need to be addressed through a structural and cultural approach.